Public willingness to pay watershed eco-compensation in China’s Taihu basin: A case study - Deng, Menghua; Li, Zhiqi; Chen, Junfei; Tao, Feifei (Frontiers in Environmental Science, 2022)
Eco-compensation is effective in promoting the sustainable development of a watershed. The exploration of the public’s willingness to pay for such compensation, along with the corresponding influencing factors, are important for improving the efficacy of eco-compensation programs. However, motivating the public to participate in eco-compensation remains a challenge. In this study, the influencing factors behind public willingness to participate in eco-compensation in China’s Taihu Basin are measured using a contingent valuation method and a random forest model. The main results are as follows: 1) In the Taihu Basin, the mean people are willing to pay for eco-compensation is 287.344 CNY/person/year. 2) The significant factors influencing willingness to pay are recognition of the importance of watershed protection; the impact of the watershed environment on people’s lives; annual incomes; and perceived improvements to the watershed environment over the past five years. 3) Awareness of the need for environmental protection can encourage people to pay eco-compensation. This study provides references that governments can use to formulate and implement eco-compensation policies and hence promote public participation in those policies.